Development of composite films based on thermoplastic starch and cellulose microfibrils from Colombian agroindustrial wastes - Montoya Rojo, Ursula Maria (2014)
Composite materials are produced using thermoplastic starch reinforced with cellulose microfibrils. The cellulose microfibrils are isolated from two different sources and their reinforcement capacity was evaluated. Vegetable cellulose (VC) microfibrils are isolated from vascular bundles of banana rachis, while bacterial cellulose (BC) microfibrils are produced by Gluconacetobacter genus bacteria using pineapple peel juice as the culture media. For this study, both the materials were obtained from Colombian agroindustrial wastes. Composite films were characterized using different techniques, including mechanical tensile testing, attenuated total reflection Fourier transform infrared spectroscopy, and thermogravimetric analysis. The purpose of this study is to assess the effect of different processing methods and cellulose microfibrils content in the composite material behavior. The results showed that the mechanical properties were increased when cellulose microfibrils were added before gelatinization. Significant increments in Young’s modulus and tensile strength of both VC and BC composites were obtained with respect to starch matrix.